Uji In Vitro Beberapa Kombinasi Antibiotik Antipseudomonas terhadap Pseudomonas aeruginosa yang Resisten terhadap Karbapenem - Prasetyo, Dimas Seto; Herna, Herna; Mursinah, Mursinah; Ibrahim, Fera; Bela, Budiman (Jurnal Kefarmasian Indonesia, 2022)
Lower respiratory tract, sepsis, or urinary tract infection caused by the multidrug resistance Pseudomonas aeruginosa is common in the hospital, especially in the ICU wards. The treatment against this bacteria requires combination of antibiotics with different mechanism of actions. In this study, several combinations of antibiotics were evaluated in vitro against carbapenem-resistant P. aeruginosa isolated from the ICU of Cipto Mangunkusumo Hospital. The combination of antibiotics tested were ceftazidime-amikacin, ceftazidime-ciprofloxacin, and ciprofloxacin-amikacin. Checkerboard assay to the combination of antibiotics was conducted to assess the in vitro synergistic activity. A total of 22 P. aeruginosa isolates were collected, 16 of them were resistant to ceftazidime, ciprofloxacin, amikacin, as well as carbapenem. The result revealed that the combination of ceftazidime and amikacin showed promising synergistic activity. Conversely, no synergitic activities were shown by the combination of ceftazidime-ciprofloxacin and ciprofloxacin-amikacin. The combination of ceftazidime-amikacin may has potential effect againsts carbapenem-resistant P. aeruginosa in vitro.